Purification and Characterization of Human ISDll - Kletzien, Otto (My University, 2014)
Iron-Sulfur clusters, a class of cofactor used in all domains of life, play crucial roles in several physiological processes. Although many proteins of the human isc Fe-5 biosynthesis pathway have been identified, many of their structures remain unsolved and several crucial steps in the pathway remain unknown. In the first step of the isc pathway, the cysteine desulfurase NFSl requires an interaction with the adaptor protein ISDll to transfer elemental sulfur to a scaffold. Although NFSl has been well characterized in previous studies, no structure has yet been obtained for ISDll. In this thesis, recombinant expression of human ISDll in E. coli and Pichia pastoris is presented. While removal of a solubility tag from ISDll proved troublesome, expression in a vector with no solubility tag enabled purification of enough ISDll for NMR. A recent 2-dimensional HSQC spectrum indicates that ISDll adopts 1 conformation in solution.